2002
DOI: 10.1002/bit.10444
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen (HBsAg) expression in plant cell culture: Kinetics of antigen accumulation in batch culture and its intracellular form

Abstract: The production of edible vaccines in transgenic plants and plant cell culture may be improved through a better understanding of antigen processing and assembly. The hepatitis B surface antigen (HBsAg) was chosen for study because it undergoes substantial and complex post-translational modifications, which are necessary for its immunogenicity. This antigen was expressed in soybean (Glycine max L. Merr. cv Williams 82) and tobacco NT1 (Nicotiana tabacum L.) cell suspension cultures, and HBsAg production in batch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 42 publications
2
66
0
Order By: Relevance
“…Dimers are then transported to the post-ER, pre-Golgi compartment where oligomerization and VLP formation occur prior to secretion [56]. For plant systems, HBsAg dimer formation was demonstrated by Western blot of protein extracts from cultured plant cells [53,57] and from infiltrated leaves [58], indicating that plants can provide a suitable environment for correct processing of HBsAg. The ability of plant-produced HBsAg to assemble VLPs was determined by sucrose gradients and electron microscopy.…”
Section: Hepatitis B Surface Antigen (Hbsag)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dimers are then transported to the post-ER, pre-Golgi compartment where oligomerization and VLP formation occur prior to secretion [56]. For plant systems, HBsAg dimer formation was demonstrated by Western blot of protein extracts from cultured plant cells [53,57] and from infiltrated leaves [58], indicating that plants can provide a suitable environment for correct processing of HBsAg. The ability of plant-produced HBsAg to assemble VLPs was determined by sucrose gradients and electron microscopy.…”
Section: Hepatitis B Surface Antigen (Hbsag)mentioning
confidence: 99%
“…Production of HBsAg in plant cell culture systems has also been attempted. The yield of HBsAg approached 22 mg/L in soybean culture while it was one tenth of that in tobacco culture [53]. NT1 cell lines were used to express S gene either with or without a C-terminal ER retention signal [54].…”
Section: Hepatitis B Surface Antigen (Hbsag)mentioning
confidence: 99%
“…In tobacco cell suspension cultures, HBsAg production achieved 2 µg g -1 of HBsAg fresh weight [29]. Cell suspension cultures of soybean were reported to produce a maximum of 20-22 mg L -1 of HBsAg [30]. Constitutive expression of HBsAg in recombinant Saccharomyces cerevisiae generated approximately 10 mg L -1 by fed-batch fermentation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Besides using different plants, Shekhawat et al (2010) (Smith et al, 2002) this study proved promising for further investigations of stable HBsAg expression in suspension cells of sandalwood.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Since the first reported plant-made HB Ag in A. tumefaciens strain LBA4404-transformated tobacco by Mason et al (1992) there has been a huge research on expressing major HBV viral proteins. Recombinant HBsAg has been expressed in lupine and lettuce (Kapusta et al, 1999), carrot suspension cells (Zhao et al, 2002), soybean (Smith et al, 2002), peanut (Chen et al, 2002), tomato (Ma et al, 2002;Carolina and Francisco, 2004;Wang and Li, 2008;Srinivas et al, 2008), cherry tomatillo (Gao et al, 2003;Guan et al, 2010), potato (Shulga et al, 2004), banana (Sunil-Kumar et al, 2005), apple core and leaves and tomato (Lou et al, 2005), NT-1 cells of tobacco (Sunil-Kumar et al, 2007) and lettuce (Kostrzak et al, 2011). Chen et al (2002) reported a high level expression of HBsAg in peanut, obtained by Agrobacterium-mediated transformation, with the yield of 2.42 µg HBsAg/g of fresh weight.…”
Section: Hepatitis Bmentioning
confidence: 99%